Occurrence of Paratanaisia confusa Freitas, 1951 in free-living guira cuckoo (Guira guira, Cuculiformes: Crotophagidae) - de Santi, Mariele [UNESP]; André, Marcos Rogério [UNESP]; Hoppe, Estevam Guilherme Lux [UNESP]; Werther, Karin [UNESP] (FapUNIFESP (SciELO), 2017)
This report presents a description of natural infection of an adult free-living guira cuckoo with Paratanaisia confusa. Histological and morphological evaluations of renal and parasite samples were performed. The morphological analysis of the parasites revealed spiny tegument, characteristic of P. confusa helminthes. Although macroscopic alterations were absent in the kidneys, the histopathology revealed parasites inside the collecting ducts causing dilatation and destruction of the lining epithelial cells in addition to small focal inflammatory infiltrates in the renal parenchyma. However, as the bird was free-living and naturally infected it was not possible to confirm if all these alterations were directly caused by the parasite presence or if they were related to causes other than the parasitism. Nonetheless, such findings indicate that these trematodes may have pathogenic potential in this host.
Ocorrência de Paratanaisia confusa Freitas, 1951 em anu-branco de vida livre (Guira guira, Cuculiformes: Crotophagidae)
Keywords: Digenea; Eucotylidae; Histopathology; New host record; Trematoda